2020
DOI: 10.4491/eer.2020.043
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting oxidation and enhancing absorption characteristics of sodium sulfite for SO2 removal from the non-ferrous smelting flue gas

Abstract: In this work, we investigated the absorption characteristics of SO2 and the effect of inhibitors on the desulfurization performances of Na2SO3. The results showed that the NO2 had a competitive effect with SO2 on SO32- which resulted in a significant decrease in the absorption capacity of SO2. O2 in the flue gas could decrease the absorption capacity of SO2 due to the oxidation of Na2SO3. Besides, Na2S2O3 had more excellent inhibiting effect on the oxidation of SO32-; the inhibition mechanism is understood on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…S 2 O 3 2– can also inhibit the chain reaction. S 2 O 3 2– reacts with • SO 3 – to generate • S 2 O 3 – , and further generates inert substances, as shown in eqs – . The effect of Na 2 S 2 O 3 on the circulating Na 2 SO 3 absorption system was studied.…”
Section: Absorbent Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…S 2 O 3 2– can also inhibit the chain reaction. S 2 O 3 2– reacts with • SO 3 – to generate • S 2 O 3 – , and further generates inert substances, as shown in eqs – . The effect of Na 2 S 2 O 3 on the circulating Na 2 SO 3 absorption system was studied.…”
Section: Absorbent Evaluationmentioning
confidence: 99%
“…, and further generates inert substances, as shown in eqs R18−R20. 45 The effect of Na 2 S 2 O 3 on the circulating Na 2 SO 3 absorption system was studied. The intrinsic oxidation kinetics results showed that the reaction order of Na 2 S 2 O 3 was −2.22, and the reaction order of Na 2 SO 3 was 2.393.…”
Section: Reducing the Degree Of Oxidation In Sodium-based Buffer Solu...mentioning
confidence: 99%
“…The ion chromatography analysis results suggest that the increase in O 2 concentration led to an increase in the oxidation of SO as shown in Eq. (10-12)[25][26][27]. Therefore, the increased HSO 3…”
mentioning
confidence: 98%